ByzRev 05.2023.010: Georgios Gusguriotes (Γεώργιος Γουσγουριώτης), Οι επιστολές του Θεοδώρου Ποτάμιου.: Thessalonike: Stamules 2022. - Grünbart, Michael (The Byzantine Review, 2023)
Georgios Gusguriotes (Γεώργιος Γουσγουριώτης), Οι επιστολές του Θεοδώρου Ποτάμιου. Thessalonike: Stamules 2022. 166 S. – ISBN 978-960-656-111-5